1988
DOI: 10.1101/gad.2.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-sensitive v-sea transformed erythroblasts: a model system to study gene expression during erythroid differentiation.

Abstract: The isolation and characterization of a temperature-sensitive mutant (tsl S 13) of the avian erythroblastosis virus, S13, is described. The temperature-sensitive lesion in tsl S13 was identified as affecting the tyrosine kinase activity but not the plasma membrane localization of the tsl S13 v-sea gene product. Erythroblasts transformed by tsl S13 can be induced to synchronously differentiate into erythrocytes in an erythropoietin (EPO)-dependent fashion. Analysis of erythrocyte-specific gene expression in tsl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…All erythroid progenitors express relatively high levels of c-Kit. Thus, endogenous c-Kit is a likely candidate to substitute for tyrosine kinase oncoproteins (v-ErbB, v-Sea) shown to cooperate with v-ErbA in earlier studies Knight et al, 1988). The ®nding that a novel type of retrovirus expressing very high v-ErbA levels was able to cause leukemia in the absence of an exogenous tyrosine kinase (Casini and Graf, 1995) is most likely also explained by cooperation of v-ErbA with c-Kit, since cKit expressing proerythroblasts bind to stromal cells during erythropoiesis in vivo which express a membrane-bound version of the c-Kit ligand (Nibbs et al, 1993).…”
Section: Cooperation Of V-erba With Activated Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…All erythroid progenitors express relatively high levels of c-Kit. Thus, endogenous c-Kit is a likely candidate to substitute for tyrosine kinase oncoproteins (v-ErbB, v-Sea) shown to cooperate with v-ErbA in earlier studies Knight et al, 1988). The ®nding that a novel type of retrovirus expressing very high v-ErbA levels was able to cause leukemia in the absence of an exogenous tyrosine kinase (Casini and Graf, 1995) is most likely also explained by cooperation of v-ErbA with c-Kit, since cKit expressing proerythroblasts bind to stromal cells during erythropoiesis in vivo which express a membrane-bound version of the c-Kit ligand (Nibbs et al, 1993).…”
Section: Cooperation Of V-erba With Activated Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…To generate primary erythroblasts, chicken bone marrow cells were doubly infected with the S13 virus, encoding the temperature-sensitive ts-vSea protein kinase (34) together with the different SFCV/R-CAS-EpoR viral stocks as described previously (28). Infected bone marrow cells were seeded in CFU-E-methocel supplemented with 100 ng/ml recombinant chicken SCF, 1.4 nM insulin (Novo-Nordik), and 2.7 mg/ml G418.…”
Section: Dna Constructs and Generation Of Recombinant Retroviruses-mentioning
confidence: 99%
“…Due to the fusion with viral envelope domain, the env-sea protein has a structure similar to RTKs (12). Previous studies showed that the env-sea tyrosine kinase activity is necessary for transformation by the env-sea protein (13) and that cell surface localization, oligomerization by viral envelope domains, and autophosphorylation are all necessary for the transforming activity of the env-sea protein (14 -16). Using a temperature-sensitive mutant, previous work demonstrated that the phosphorylation of the Shc proteins correlated with the activation of the tyrosine kinase activity of the env-sea protein (17).…”
mentioning
confidence: 99%